2019
DOI: 10.3390/app9091842
|View full text |Cite
|
Sign up to set email alerts
|

Species of the Genus Salix L.: Biochemical Screening and Molecular Docking Approach to Potential Acetylcholinesterase Inhibitors

Abstract: The genus Salix includes about 500 different, mainly woody species with potentially significant medicinal values. The aim of this study was to evaluate the chemical composition and antioxidant activity of little-studied bark and leaves extracts of seven different species of the genus Salix, and to examine the acetylcholinesterase (AChE) inhibitory potential of selected compounds. The extracts were characterized by High Pressure Liquid Chromatography (HPLC). Total phenolics and flavonoids content was determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 37 publications
0
36
1
Order By: Relevance
“…There are many studies showing that Salix alba bark is a natural source of phenolic compounds with antioxidant activity [8,9,11]. Compared to data reported by [6] on total phenolic content of ethanolic extracts of S. alba bark, our results are 2.4 times higher. Also, ethanolic extract of S. alba and S. purpurea bark are reported to contain important concentration of phenolic compounds [23].…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…There are many studies showing that Salix alba bark is a natural source of phenolic compounds with antioxidant activity [8,9,11]. Compared to data reported by [6] on total phenolic content of ethanolic extracts of S. alba bark, our results are 2.4 times higher. Also, ethanolic extract of S. alba and S. purpurea bark are reported to contain important concentration of phenolic compounds [23].…”
Section: Discussioncontrasting
confidence: 65%
“…The parts of willow species which can be used are mainly represented by bark and leaf. Besides the salicin content, willow also represents a source of bioactive compounds, including polyphenols and flavonoids, with significant implications in fulfilling the curative roles of willow [6].…”
Section: Introductionmentioning
confidence: 99%
“…The differences between the present results and those reported by Sulaiman et al (2013) may be because differences in solvents that were used in extraction (grain/water as opposed to boiled ethanol), the extraction method (hydro-alcoholic extraction as opposed to Soxhlet), extraction time, and environmental factors. Many researchers have reported major differences in the concentration of polyphenols of willow bark extracts (Durak & Gawlik-Dziki, 2014;Zabihi et al, 2018;Gligoric et al, 2019). Among the causes of their differences are the part of product that was used and the Salix species.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding tannin content, it was concluded that SBPE has 1.14% and BBPE has 1.47% [19]. The results showed that the beech bark extracts contained considerable quantities of aromatic compounds, such as (+)-catechin, (−)-epicatechin, quercetin-O-hexoside, taxifolin-O-hexosides, taxifolin-O-pentosides, B-type and C-type procyanidins, syringic acid, and coumaric acid-di-O-glycosides, coniferyl alcohol and sinapyl alcohol-glycosides, and (+) and (−) glucodistylin [11,18,19]. The compounds identified in spruce bark extract by HPLC were gallic acid (3.19 mg GAE/100 g), catechine (31 mg GAE/100 g), and vanillic acid (39.4 mg GAE/100 g) [13].…”
Section: Extracts Characterizationmentioning
confidence: 99%
“…Polyphenols have a significant role in the protection of living cells against biotic (fungi, infections, diseases) and abiotic (wounds, drought, and pollution) factors. Polyphenols are known for their antioxidant capacity [11,12]. The effects of polyphenolic extracts as antioxidant agents, plant growth regulators, or bioremediation agents have been successfully tested [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%